2000
DOI: 10.1078/s0031-4056(04)70073-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vermicomposts and composts on plant growth in horticultural container media and soil

Abstract: E Ef ff fe ec ct ts s o of f v ve er rm mi ic co om mp po os st ts s a an nd d c co om mp po os st ts s o on n p pl la an nt t g gr ro ow wt th h i in n h ho or rt ti ic cu ul lt tu ur ra al l c co on nt ta ai in ne er r m me ed di ia a a an nd d s so oi il l SummaryVermicomposts, which are produced by the fragmentation of organic wastes by earthworms, have a fine particulate structure and contain nutrients in forms that are readily available for plant uptake. In greenhouse trials, the growth of marigold and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
220
2
37

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 367 publications
(277 citation statements)
references
References 21 publications
18
220
2
37
Order By: Relevance
“…Atiyeh et al (2000) reported that the shoot dry weights of raspberry plant soil mixed with vermicomposted pig wastes weighted more than those grown in unfertilized control soil, and were as great as those in soil receiving a chemical fertilizer treatment.…”
Section: Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Atiyeh et al (2000) reported that the shoot dry weights of raspberry plant soil mixed with vermicomposted pig wastes weighted more than those grown in unfertilized control soil, and were as great as those in soil receiving a chemical fertilizer treatment.…”
Section: Treatmentsmentioning
confidence: 99%
“…Several studies have examined growth of plants using vermicompost derived from different materials in green house conditions or in field studies (Atiyeh et al 2000). All such studies indicated beneficial effects of vermicompost on plant growth.…”
Section: Introductionmentioning
confidence: 99%
“…The changes result from the addition of a large number of base cations to the soil at the time of fertilization (Orozco et al 1996;Atiyeh et al 2000aAtiyeh et al , 2000b and to the fact that crops selectively absorb ions, such as hydrogen ions. After seven cucumber crops, the application of VP amendment resulted in decreased soil pH that differed from those after FT and FC amendments.…”
Section: Effects Of Vermicompost Application On Soil Propertiesmentioning
confidence: 99%
“…Por otra parte, la vermicomposta es un abono producto de la transformación de residuos orgánicos realizada por lombrices. Tiene una estructura fina y contiene nutrientes en formas que son inmediatamente disponibles a las plantas (Atiyeh et al, 2000).…”
Section: Introductionunclassified
“…Moreover, the fertilizer product is vermicompost transformation of organic waste by earthworms. It has a fine structure and contains nutrients in forms that are readily available for the plants (Atiyeh et al, 2000).…”
Section: Introductionmentioning
confidence: 99%